ANTITUBERCULOSIS ACTIVITY OF METHANOLIC EXTRACT OF KEDONDONG HUTAN (SPONDIAS PINNATA (L.f.) Kurz.) LEAVES - Ida Bagus Nyoman Putra Dwija; I Ketut Juniarta; Sagung Chandra Yowani; Ni Putu Ariantari (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
Tuberculosis remains global health problem nowadays. The presence of resistant strain of Mycobacterium tuberculosis against first and second line antiberculosis drugs, support any effort for discovering alternative and complementary therapy. Kedondong Hutan (Spondias pinnata (L.f) Kurz.) belongs to Anacardiaceae family, traditionally used to treat chronic cough, which is one of common symptoms of tuberculosis. The objective of this study was to investigate antituberculosis activity of methanolic extract of Kedondong hutan leaves against multidrug resistant strain of M. tuberculosis. Kedondong hutan leaves were extracted with methanol continued with phytochemical analysis. Antituberculosis activity assay of this extract was performed by proportion method using L-J medium. Extract was tested within 3 different concentration of 10, 50 and 250 mg/mL, with and without any additional rifampicin of 40 µg/mL. The observation of colonies was done every day started from 3rd week until 4th week and then analyzed qualitatively. The result of phytochemical analysis showed the presence of triterpenoids and flavonoids. Antituberculosis activity of kedondong hutan leaves extract at a concentration of 30 mg/mL was 52-73% and that ofcombination of 10 mg/mL extract + 40 µg/mL rifampicin was 85-89.5%. Extract concentration of 50 and 250 mg/mL, alone and combined with rifampicin showed growth inhibiton of 100%. In conclusion, methanol extract of kedondong hutan leaves has a potential antituberculosis activity.